Fluorinated alcohol as Pickering emulsion demulsifier - Hiroki Matsubara; Seiya Ito; Shinji Masaoka (Next Materials)
This short paper examines the effectiveness of a fluorinated alcohol (1 H,1 H,2 H,2H-perfluorodecanol: FC10OH) as demulsifiers for Pickering emulsions by assessing interfacial tension and visually observing the stability of the emulsified samples. The Pickering emulsions were created using hydrophilic spherical silica particles and hydrophobic carbon black. When dodecane was used as the oil phase, O/W and W/O Pickering emulsions were formed, respectively. It was verified that the addition of FC10OH in oil phase led to their spontaneous demulsification. This occurrence is attributed to the fact that FC10OH reduces the oil-water interfacial tension more effectively than these particles. In other words, FC10OH has a greater tendency to adsorb at the oil-water interface compared to particles, which causes the detachment of particles from the interface, thereby resulting in Pickering emulsion demulsification.